áanzho ha’shi ‘dał’k’ida’, ‘áá’áná’, ‘doo maanaashni’: Welcoming ‘long ago’, ‘way back’ and ‘remember’—as an Ndé decolonization and land recovery process - Tamez, Margo (InTensions, 2012)
Memory, re-membering, oral history and critical recovery are pillars of a Ndéi decolonization and self-determination process in indigenous peoples’ rancherías along the Lower Rio Grande River and Texas-Mexico border. The goals of this process are to dismantle the U.S. border wall bifurcating the customary lands of indigenous peoples; to reclaim dispossessed lands; and to revitalize Ndé ways of life in autonomy and self-governance. In the Ndé language, we can communicate in this way about a recovery process, Dáanzho ha’shi ‘dał’k’ida’ áá’áná ‘doo maanaashni’—‘long ago, way back’ and gain knowledge, insights and tools from our foremothers’ and forefathers’ struggles and resistance strategies. In October 2009, when the U.S. violently coerced and forced vulnerable peoples off the community lands along the Texas-Mexico border, and obstructed international covenants, treaties, and human rights laws, the discursive legal fiction of ‘terrorism’ was deployed to launch a massive land grab. At this stage, however, indigenous peoples along the Lower Rio Grande River were already involved in an ongoing process of restoring and implementing Ndé law and governance systems based upon women’s traditional knowledge and historical experiences in land defense.